Lifestyle and faith practice of migrant Catholics in Vietnam: Adaptation and contribution in the renovation period in Hanoi, Vietnam - Thi, Ha Vu (Edelweiss Applied Science and Technology, 2024)
This study explores the lifestyle and faith practices of Catholic migrants from rural dioceses, such as Bùi Chu and Vinh, to Hanoi during Vietnam's Renovation (Đổi Mới) period. As Vietnam experienced rapid urbanization and socioeconomic transformation, these migrants navigated significant challenges adapting to urban life while preserving their religious and cultural identities. The research highlights their adaptation strategies, including establishing support networks, adjustments in spiritual practices, and participation in urban labor markets. It also examines their contributions to Hanoi’s development, emphasizing their economic impact, cultural enrichment, and efforts in fostering social solidarity. Despite their resilience and resourcefulness, Catholic migrants face obstacles such as housing insecurity, limited labor protections, and the pressure to balance traditional faith practices with urban demands. The study concludes with policy recommendations to enhance the support for migrant communities, including affordable housing programs, labor protections, and more vital collaboration between the Church, government, and society. By addressing these challenges, Hanoi can harness the full potential of Catholic migrants as integral contributors to its social and economic development.